Net primary productivity of Bruguiera parviflora (Wight & Arn.) dominated mangrove forest at Kuala Selangor, Malaysia - Hossain, Mahmood; Othman, Saberi; Bujang, Japar Sidik; Kusnan, Misri (2008)
The net primary productivity of Bruguiera parviflora dominated mangrove forest at Kuala Selangor, Malaysia was estimated from the average yearly biomass increment and litter production. The average yearly biomass increment in saplings and trees was 0.58 and 16.51 t ha−1, respectively, and the annual amount of total litter production was 10.35 t ha−1. The biomass increment in saplings and trees was not significantly different (t-test, p > 0.05) in 2 successive years and the estimated net primary productivity was 27.44 t ha−1 year−1. The ratio (2.65:1) of net primary productivity and litterfall suggests that this mangrove forest is at a juvenile stage.